Evaluation of Beliefs About Hypertension in a General Population - Sarah McBane PharmD, CDE, BCPS; Brian Halstater MD (SAGE Publishing, 2011)
Purpose : Hypertension affects millions of people in the United States, yet many do not reach their blood pressure goals. Existing data indicate that self-management skills improve chronic disease management. Beliefs and attitudes are an important component of self management. This pilot study was designed to evaluate the beliefs of the general public on hypertension. Methods : One hundred patients of Duke Family Medicine were verbally consented to receive a survey consisting of 16 true/false questions. Included subjects were 18 years and older and comfortable answering questions in English. The questions addressed self-management behaviors, definition, and complications of hypertension. Basic demographic data were collected. Descriptive statistics were performed on the data. Results : Of 120 patients screened, 100 met inclusion criteria and agreed to participate in the study. Demographic data indicated that surveyed subjects were similar to the general clinic population: 69% were women, 51% African American, and 55% age 45 years and older. A total of 79% of subjects answered 13 or more questions correctly. The 3 most commonly missed questions addressed fatality of hypertension, adverse effects of medications, and potential for curing hypertension. Conclusion : Hypertension is a prevalent issue affected by many factors. Beliefs of the general population, including the role of self-management, seem consistent with current medical knowledge. However, this study only evaluated beliefs not behaviors of patients. Further study is needed to elucidate patient-oriented factors that may limit control of hypertension.